Validación del comportamiento del acero AISI SAE 1045 sometido a fatiga por flexión rotativa a bajas temperaturas bajo la norma ASTM E606. (2023)
The development of this research project is part of a validation study of the mechanical behavior of AISI SAE 1045 steel when subjected to dynamic loads by rotary bending to evaluate fatigue at temperatures of 0, -3, and -5 degrees Celsius, temperatures that can affect the steel's structure and therefore alter its ductility.